Redox-responsive alginate nanogels with enhanced anticancer cytotoxicity - Maciel, Dina (2019)
Although doxorubicin (Dox) has been widely used in the treatment of different types of cancer, its insufficient cellular uptake and intracellular release is still a limitation. Herein, we report an easy process for the preparation of redox-sensitive nanogels that were shown to be highly efficient in the intracellular delivery of Dox. The nanogels (AG/Cys) were obtained through in situ cross-linking of alginate (AG) using cystamine (Cys) as a cross-linker via a miniemulsion method. Dox was loaded into the AG/Cys nanogels by simply mixing it in aqueous solution with the nanogels, that is, by the establishment of electrostatic interactions between the anionic AG and the cationic Dox. The results demonstrated that the AG/Cys nanogels are cytocompatible, have a high drug encapsulation efficiency (95.2 ± 4.7%), show an in vitro accelerated release of Dox in conditions that mimic the intracellular reductive conditions, and can quickly be taken up by CAL-72 cells (an osteosarcoma cell line), resulting in higher Dox intracellular accumulation and a remarkable cell death extension when compared with free Dox. The developed nanogels can be used as a tool to overcome the problem of Dox resistance in anticancer treatments and possibly be used for the delivery of other cationic drugs in applications beyond cancer.